Charge-induced electrochemical actuation of armchair carbon nanotube bundles. (July 2017) - Hung, Nguyen T.; Nugraha, Ahmad R.T.; Saito, Riichiro
Abstract: The effects of charge doping on the structural deformation and on the electronic structure of armchair single wall carbon nanotube (SWNT) bundles are investigated through first-principles calculations. In particular, we select a ( 6, 6 ) SWNT as an example and we calculate a mechanical deformation in the SWNT bundles as a function of gate voltage, which could serve as a basis of the electromechanical actuators in an artificial muscle. We find that the magnitudes of the actuation responses such as strain and stress of the ( 6, 6 ) SWNT bundle in the case of hole doping are substantially larger than those of electron doping. The ( 6, 6 ) SWNT bundle also exhibits a low-symmetry and opens an energy band gap of about 0.41 eV around the charge neutral condition, which allows a semiconductor-to-metal transition in the electron-doping regime when the relative shift of the Fermi energy goes up to 0.60 eV, above which the Young modulus increases. Graphical abstract: